1157. Clinical Safety, Efficacy, and Pharmacokinetics of Fosmanogepix, a Novel First-in-class Antifungal, in Patients with Renal Insufficiency: Subset Analysis from a Phase 2 Candidemia Trial. (31st December 2020) - Bulpa, Pierre; Rahav, Galia; Oren, Ilana; Aoun, Mickaël; Thompson, George R; Pappas, Peter; Kullberg, Bart Jan; Vazquez, Jose A; Barbat, Sara; Wedel, Pamela; Schlamm, Haran T; Hodges, Michael
Abstract: Background: Fosmanogepix (FMGX) is a first-in-class antifungal agent, with a unique MOA targeting the fungal enzyme Gwt1, and broad-spectrum activity against yeasts and molds, including fungi resistant to other antifungal agents. Patients with candidemia often have underlying renal insufficiency or are receiving medications that affect renal function. This analysis evaluated outcomes in patients with varying degrees of renal insufficiency. Methods: This global, multicenter, open-label, non-comparative study evaluated the safety and efficacy of FMGX for first-line treatment of candidemia. Patients with a recent diagnosis of candidemia defined as positive blood culture for Candida spp within 96 hrs prior to study entry with ≤ 2 days of prior antifungal treatment were eligible, including those with renal insufficiency. Patients with neutropenia, C. krusei infection, deep-seated Candida infections or receiving hemodialysis were excluded. Subjects were treated with FMGX for up to 14 days: 1000 mg IV BID for 1 day, then 600 mg IV QD for at least 2 days, followed by either 600 mg IV QD or 700 mg PO QD. Patients requiring antifungal treatment beyond 14 days received fluconazole. The primary efficacy endpoint was outcome at end of study treatment (EOST) as determined by an independent data review committee. Successful outcome was defined as survival with clearance of Candida from blood cultures with no additional antifungal treatment. Results: 14/21 (66%) subjects had some degree of renal insufficiency: 7 had mild renal insufficiency (GFR:60-89), 5 had moderate renal insufficiency (GFR:30-59), and 2 had severe renal insufficiency (GFR:15-29). 12/14 (86%) completed study treatment, and treatment was successful at EOST in 12/14 (86%) subjects. Decline in renal function was not observed at EOST. 4 had worsening of renal function during the follow-up period; none required dialysis. Renal impairment did not increase exposure of FMGX. There were no treatment-related adverse events. Conclusion: FMGX demonstrated high level treatment success with no evidence of drug-related nephrotoxicity, with no dose adjustments required. These preliminary data support the continued evaluation of FMGX in patients with candidemia and renal dysfunction as an alternative to potentially nephrotoxic antifungal agents. Disclosures: Pierre Bulpa, MD, Amplyx Pharmaceuticals (Scientific Research Study Investigator) Galia Rahav, MD, AstraZeneca (Scientific Research Study Investigator) Mickaël Aoun, MD, Amplyx Pharmaceuticals (Scientific Research Study Investigator) Peter Pappas, MD, SCYNEXIS, Inc. (Consultant, Advisor or Review Panel member, Research Grant or Support) Bart Jan Kullberg, MD, FRCP, FIDSA, Amplyx (Advisor or Review Panel member) Sara Barbat, BSN, RN, Amplyx Pharmaceuticals (Employee) Pamela Wedel, BSc, Amplyx Pharmaceuticals (Employee) Haran T. Schlamm, MD, Amplyx (Consultant) Michael Hodges, BSc. MD, Amplyx Pharmaceuticals Inc. (Employee)